Experiences with stopping inflation - Yeager, Leland B. (Washington : American Enterprise Institute for Public Policy Research, 1981)
This book surveys eighteen historical episodes in which inflation was stopped or nearly stopped. Six of these episodes were concerned with ending hyperinflations, five with pulling back from the brink of hyperinflation, three with anti-inflation programs in Latin American countries since World War 11, and four with greatly reducing inflations of largely external origin in the 1970s.
Includes index.
Includes bibliographical references.
usc 14/05/18
Loans
Keywords: Inflation (Finance); Stopping inflation